Pulse shape discrimination in CUPID-Mo using principal component analysis. (22nd March 2021) - Huang, R.; Armengaud, E.; Augier, C.; Barabash, A.S.; Bellini, F.; Benato, G.; Benoît, A.; Beretta, M.; Bergé, L.; Billard, J.; Borovlev, Yu. A.; Bourgeois, Ch.; et al.
Abstract: CUPID-Mo is a cryogenic detector array designed to search for neutrinoless double-beta decay (0νββ) of 100 Mo. It uses 20 scintillating 100 Mo-enriched Li2 MoO4 bolometers instrumented with Ge light detectors to perform active suppression of α backgrounds, drastically reducing the expected background in the 0νββ signal region. As a result, pileup events and small detector instabilities that mimic normal signals become non-negligible potential backgrounds. These types of events can in principle be eliminated based on their signal shapes, which are different from those of regular bolometric pulses. We show that a purely data-driven principal component analysis based approach is able to filter out these anomalous events, without the aid of detector response simulations.